Multimodal Biometric Analysis: Exploring Lip Print, Fingerprint, and Blood Group Correlations in the Firozabad Populations - Shailja Singh; Kimee Hiuna Minj; Sana Jamal; Sameer Saharan; Priyakanksha Mishra; Pushplata Singh; Vaishali Sinha (Journal of Forensic Science and Medicine)
Aim: This study aimed to establish a relationship between blood groups, fingerprint types, and lip prints that can be utilized to distinguish between genders when identifying a person. Materials and Methods: The study was conducted among 200 female and male participants ages 28 of Firozabad-based populations. Along with the blood types, finger, and lip print patterns were also gathered. For statistical analysis, SPSS Normal H. Nie, standford, california, united states was employed. The qualitative factors’ frequency and percentages were determined. Results: In the present study, overall Type II lip print in males and Type III lip print in females, loop fingerprint pattern and blood group O(+)ve in both sexes were most prevalent, and our findings were matched with the study of Harsha and Jayaraj, in which Type II (39.9%), loops 27 (42.2%), and blood group O(+)ve were observed predominantly. Conclusion: Personal identification of an individual can be greatly aided by personal characteristics such as blood group type, fingerprints, and lip prints. The most frequent patterns in our study were the Type II lip pattern in the males and Type III lip pattern in females, blood group O+, and the loop fingerprint pattern.